Marketing Intelligence And Sustainable Competitive Advantage Of Selected Small And Medium Scale Businesses In Ekiti: An Overview Babatunde - BABATUNDE, Eniola Moyinoluwa (Archives of Business Research, 2020)
The study examined the effect of marketing intelligence on the sustainance of competitive advantage among Small and Medium Scale businesses in Ekiti State. Specific objectives investigated in this study are competitors’ threat; and competitive risk and their influences on sustainable competitive advantage in Small and Medium Scale businesses. The target population of the study comprised of 84 SMEs operators in Oye-Ekiti Local Government Area of Ekiti State, Nigeria as registered with Ministry of Commerce, Industries and Cooperatives, Ekiti State. The sample size of the study is 69 respondents. Frequency and percentages were used for descriptive statistics respondents to view questions of research instrument. Inferential statistics were also used to achieve objectives I, II and multiple regression analyses were employed to test the hypotheses. It was found that Competitor’s threat: potential competitor (p= 0.013). Competitive risk: Marketplace Change (p= 0.000), Intelligence-based assessment (p= 0.000) are determinants of sustainable competitive advantage as far as SMEs are concerned in Ekiti State. .The study concluded and revealed that salesmen do share information about competitors in the market and recommended that there should be rapid response to competitive action to achieve their goals.